Harvest Time Residues of Imidacloprid and Thiamethoxam in Black Gram - Srikanth, N.; Ahmad, Md. Abbas; Sahoo, S. K. (International Journal of Bio-resource and Stress Management, 2023)
Imidacloprid and thiamethoxam insecticides have been important tools for controlling pests in black gram. The use of these pesticides on various crops has increased rapidly resulting the produce containing toxic residues from the application of these insecticides and in some cases the concentrations are above maximum residue limit. The prudent usage of synthetic insecticides resulted in secondary pest-outbreaks, resistance development, food, and ecosystem adulteration and so on which pose serious threat to human beings. However, food safety issues related to pesticide residues are important to consider with a food crop such as black gram which causes no harm to consumers and are permissible in domestic and international trade. Therefore, the objective of this study was to analyse harvest time residues of imidacloprid and thiamethoxam in black gram. The study was conducted during the summer season 2021 at Research Farm, Tirhut College of Agriculture, Dholi (Muzaffarpur)–Bihar. The crop (cultivar SML 613) was sown on February, 27, 2021. Insecticides were applied at 30 days after sowing which was followed by two successive sprays at 15 days intervals following the recommended dose of 25 g a.i. ha-1 for both the insecticides. Sample aliquots were analysed using HPLC (High Pressure Liquid Chromatography) equipped with Photo Diode–Array Detector (PDA). The sample taken at harvest with a pre–harvest interval (PHI) of 28 days did not reveal the residues of imidacloprid and thiamethoxam in black gram seeds at Limit of Quantification (LOQ) of 0.05 mg kg-1.